PENGAWASAN KEPATUHAN PERPAJAKAN INSTANSI PEMERINTAH DESA MELALUI COMPLIANCE RISK MANAGEMENT (CRM) - Agustinus Imam Saputra; Moh Abrori Akbar (Jurnal Anggaran dan Keuangan Negara Indonesia (AKURASI), 2023)
This study aims to find out how much tax revenue comes from village government spending through analysis of Compliance Risk Management (CRM) use and mapping villages that need supervision and education in fulfilling tax obligations. This study uses a descriptive quantitative research method by presenting data on the allocation of village income and expenditure and tax payments by village government agencies nationally. The results showed that from 436 districts, there was a phenomenon of differences in the ratio of tax payments compared to the expenditure value of village treasurers with a potential state revenue of around 342 billion. Through CRM supervision of village treasurers, it was found that there were 176 KPP Pratama that had a ratio of village treasurers to tax payments below the national average or 1.658 per cent. The CRM can only predict the taxation potential of one KPP and does not provide taxation potential per village. This study uses secondary data from Indonesian statistic's 2020 and 2021 village financial reports. This study is expected to provide input for policymakers and enrich the perspective of researchers in the use of risk management in the public sector.